Two laboratory methods for diagnosis of herpes simplex keratitis. Issue 10 (October 1987) - Collum, L. M.; Mullaney, J.; Hillery, M.; Mullaney, P.; Lester, R.
Abstract : Two techniques are described which enable a rapid diagnosis of herpes simplex keratitis to be made. The tests, antibody/antigen reactions, were shown to be accurate and sensitive in the 119 patients examined. A result is available within four hours with the indirect peroxidase-antiperoxidase method and within one hour with the direct method. The techniques are relatively inexpensive, though labour intensive. Negative reactions were found in treated cases and in those with some delay in the histochemical staining.